Detection and identification of a group 16SrIII-related phytoplasma associated with coffee crispiness disease in Colombia - Galvis Garcia, CA; Leguizamon Caycedo, JE; Gaitan, AL; Mejía de los Ríos, J.F.; Álvarez, E.; Arroyave, José A. (Scientific Societies, 2007)
Coffee crispiness (“crespera”), a disease of uncertain etiology, has been endemic in coffee (Coffea arabica L.) plantations in Colombia for at least 60 years. Symptoms typically consist of bud proliferation, abundant short and narrow leaves, phyllody, floral abortion, monospermic fruit, and dwarfing of plants. In severe cases, coffee crispiness disease (CCD) can affect production significantly. In this study, association of a phytoplasma with CCD was indicated by the accumulation of Diene's stain, or 4?, 6-diamidino-2-phenylindole fluorescence, only in phloem of affected plant tissues. The presence of polymorphic phytoplasma cells in phloem sieve tube elements was confirmed by transmission electron microscopy. The disease was transmitted successfully by grafting symptomatic shoots from CCD-affected C. arabica plants onto young, healthy rootstocks; however, symptoms failed to develop after mechanical inoculation of young plants with extracts derived from diseased plant tissues. A nested polymerase chain reaction (PCR) assay employing primer pairs P1/P7 followed by FU5/rU3 amplified a 16S ribosomal DNA product (941 bp) exclusively from DNA of diseased plants. Sequence and phylogenetic analysis of the nested PCR product identified the CCD phytoplasma as a new strain member of group 16SrIII (X-disease group). This is the first report of a phytoplasma infecting coffee plants.